The Ambivalence and Lust of Marriage: With and Beyond Augustine Towards a Theology of Marriage as Consecrated Sacrifice - Ellis, Daryl (Scottish journal of theology, 2013)
This article argues that the Christian West's indebtedness to contractual logic in regard to marriage, as canonically depicted in 1 Corinthians 7, has resulted in a corresponding theological and pastoral myopia. The weakness of this reliance, as seen paradigmatically in Augustine's theology of marriage, consists in its articulation of marriage's constitution apart from any meaningful reference to the particular dynamics of any given marital common life. ‘Marriage’, in this sense, remains extrinsic to the living of marriage. Augustine doubly solidifies this separation by construing marriage as a contractually negotiated site for the sinful, though forgivable, expression of sexual desire, which he then roots in a christological account of sacrament whereby the sacramental bond of marriage can never be broken regardless of the lived particularities of marital life. A promising corrective can be found by way of a theological retrieval of a minor set of images suggestively employed in passages such as Ephesians 5:21–33 and Revelation 19:7–9 rooted in cultic themes such as sacrifice and consecration, which Augustine employs in describing marriage's preferred ecclesial alternative: the consecration of virginity. The constructive result is a theology of marriage in which every moment of marital life is marked by the ambivalence of vulnerably and ‘deathly’ surrendering to one another, which is pre-eminently embodied in the surrender of Christ himself upon the cross to the one he called Father. This ambivalence is characterised by the dual possibility, inherent in the posture of surrender itself, in which the result can either bear the healing fruits of love and reciprocal embrace or the tragic inhumanity of abuse, rejection and manipulation. Finally, the sacrificial and contractual elements of marriage might be ultimately reconciled in a refigured notion of ‘covenant’, which too often has been understood simply as a synonym for ‘contract’. Instead, a proper covenantal understanding of marriage emerges as a participatory analogy to the entire, complicated and contingent history of God, with God's people marked by seemingly endless cycles of sin, repentance, forgiveness and restoration. Intriguingly, this history was also founded within a temporal space outlined by a mix of contractual elements and cultic regulations. Likewise, the covenantal founding of a marriage mirrors a similar dynamic: the initial ‘contractual’ vows speak into existence a temporalised space within which a daily, mundane life of love might come to pass and bear its fruits, in due time, by God's grace and the daily improvisations of love and sacrifice.